Recto-vestibular fistula with colonic duplication: report of three cases and review of literature - Rajat Piplani; Samir K. Acharya; Deepak Bagga (SpringerOpen, 2022)
Abstract Background Anorectal malformations associated with colonic duplications are a rare condition. Double terminations of tubular colonic duplication in the perineum are even rarer. Colonic duplication may have different presentations according to its location and size and incidence of less than 15% of all gastrointestinal duplications. We hereby report three such cases of recto-vestibular fistula along with underlying tubular colorectal duplication over a period of 10 years (2010-2020) managed successfully by different surgical approaches. These cases also illustrate the diagnostic challenge and variable presentation of colonic duplications in female patients with recto-vestibular fistula. Case presentation Case 1 is a patient with flank heteropagus with absent anal opening and recto-vestibular fistula, while cases 2 and 3 presented as suspected H-type recto-vestibular fistula with normal anal opening. All the cases were however managed with a specific surgical approach on case basis. Duplicated colon was excised in case 1, but in case 2 and case 3, duplicated colon was converted into single channel using proximal and distal staplers. Further definitive repair of female recto-vestibular fistula was done. Conclusions Colorectal duplication is a rare congenital malformation, and their association with anorectal malformations is even rarer. This association can have varied presentation, and surgical approach should be according to the congenital anatomical variations on case-to-case basis. Colonic duplications should always be ruled out in a female newborn child with history of passage of stools both from the vestibule and anus.